The vixen : a novel - Prose, Francine, 1947- (Harper, an imprint of HarperCollinsPublishers, 2021)
In 1953 at a distinguished New York publishing firm, Simon Putnam, a recent Harvard graduate, is tasked with editing a steamy bodice-ripper based on the trial of Ethel and Julius Rosenberg--a project that makes him realize that the people around him are not what they seem.